2011
DOI: 10.1139/f2011-065
|View full text |Cite
|
Sign up to set email alerts
|

Ocean circulation, Stokes drift, and connectivity of western rock lobster (Panulirus cygnus) population

Abstract: An individual-based model, incorporating outputs of a data-assimilating hydrodynamic model, was developed to investigate the role of ocean circulation in the recruitment processes of western rock lobster ( Panulirus cygnus ) during its 9- to 11-month larval phase off the west coast of Australia. During austral summer, strong northward alongshore winds aid the offshore movement of early-stage model larvae from midshelf hatching sites into open ocean; during austral winter, eastward flows that feed the enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 37 publications
2
67
0
Order By: Relevance
“…Turbulence-induced sinking also contributed to onshore larval migration within the surf zone in a recent model that accounted for non-linear transport by surface gravity waves, known as Stokes drift (Fujimura et al, 2014). Outside the surf zone on the continental shelf, Stokes drift is often shoreward at the surface and may be an important mechanism of onshore larval transport (Monismith and Fong, 2004;Feng et al, 2011;Röhrs et al, 2014). It is unknown whether larvae can modify their behavior to exploit waves as a mechanism of delivery to coastal habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence-induced sinking also contributed to onshore larval migration within the surf zone in a recent model that accounted for non-linear transport by surface gravity waves, known as Stokes drift (Fujimura et al, 2014). Outside the surf zone on the continental shelf, Stokes drift is often shoreward at the surface and may be an important mechanism of onshore larval transport (Monismith and Fong, 2004;Feng et al, 2011;Röhrs et al, 2014). It is unknown whether larvae can modify their behavior to exploit waves as a mechanism of delivery to coastal habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on cultured phyllosomas have indicated that their prey density and temperature are key determinants for their healthy development (Tong et al 2000;Liddy et al 2004). Understanding how environmental factors affect phyllosoma health is crucial, because declining numbers of settling postlarvae has recently been described in the three largest populations of spiny lobsters in the world, causing concern for the major fisheries that they support (Ehrhardt and Fitchett 2010;Linnane et al 2010;Feng et al 2011). The most dramatic decline has been observed in the world's second-largest spiny lobster fishery, that is for the Western Australian spiny lobster, Panulirus cygnus (Brown 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, this relationship has broken down, with historically low annual settlement of pueruli being recorded regardless of the strength of the Leeuwin Current (Feng et al 2011). The cause of the breakdown in this relationship is uncertain but appears to be related to oceanographic processes (Säwström et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Western Australian lobster, Panulirus cygnus, is the basis of the world's second largest spiny lobster fishery, which has had an annual commercial catch varying between 5,899 and 14,523 t over the last 30 years before quotas were implemented (Brown 2011;Feng et al 2011). In the past, the annual catches of adult lobsters in the fishery have been correlated with the extent of settlement of post-larva (known as pueruli) to the coast 3 and 4 years earlier (Phillips 1986).…”
Section: Introductionmentioning
confidence: 99%